Boas práticas em medicações injetáveis: uma estratégia educacional digital para profissionais e estudantes de enfermagem - Roseira, Camila Eugenia (Universidade Federal de São Carlos, 2020)
Safe injection practices involve measures that prevent damage to the health of the patient and the professional, such as infections. To stimulate safe practices, the availability of educational materials addressing this theme, supported by Information and Communication Technology (ICT). The objective was to build and validate educational material for nursing professionals and students aiming at good practices in the administration of injectable medications. This study consisted of the construction and validation of the Safe Injection Practices Questionnaire (SIPQ), structured in four domains for contextualization of this scenario. The SIPQ was distributed electronically to professionals enrolled in the Regional Nursing Council of Sao Paulo. In total, 1925 professionals participated in this stage. Most professionals (41.62%) it belonged to the middle level and was active in hospital service (57.45%). In general, the answers were configured within safe practices with injectables, however, some actions mentioned presented risk to infection, since the frequency "always" was indicated by: 1.24% for the reuse of the same syringe for salinization of venous accesses of different patients; 8.26% for reuse of intravenous catheter extension plugs and 2.32% for inappropriate storage of these; 80.46% for the use of gloves for the administration of intravenous injections; 12.97% for participation in training for the handling of needles and catheters with safety devices and 20.08% for the transport of syringes and needles unprotected after use. These data supported the construction and validation of the open on-line course and without tutoring " Safe Injection Practices: actions for infection control", composed of ebook (hand hygiene and actions for infection control, such as the prohibition of reuse of inputs), podcast containing actions for the professional healthcare (use of gloves, participation in training and prevention of accidents with sharps) , forum to stimulate interaction between participants and an evaluation questionnaire for certificate issuance. The course material was validated by content, being considered adequate by all evaluators, while the questions were considered clear and pertinent. To evaluate the reaction to the course, after making this available in the Portal de Cursos Abertos (PoCA), 17 participants left their perception about it, pointing to the thematic relevance and acceptability of the tools (the forum being possibly the least attractive tool). Therefore, it was noted that most nursing professionals report Safe Injection Practices, however, there are actions that should be considered in order to subsidize safe practice. To this do so, the course built, validated and made available free of charge and openly can be used as a support tool by all those involved in the area.
Safe injection practices: a digital educational strategy for nursing professionals and students
Keywords: Estudos de validação; Cuidados de enfermagem; Injeções intramusculares; Injeções intravenosas; Educação a distância; Validation study; Nursing care; Injections intramuscular; Injections intravenous; Education distance; CIENCIAS DA SAUDE::ENFERMAGEM